Solid Media (Lowenstein Jensen) and Liquid Media (Mycobacteria Growth Indicator Tube) Usage Against Mycobacterium tuberculosis Culture in Sputum Suspect Tuberculosis - Pestariati Pestariati; Meilinda Rachmawati (Humanistic Network for Science and Technology (HNST), 2021)
Tuberculosis examination using Lowenstein Jensen (LJ) media, requires an incubation time of 8 weeks after inoculation. The objective of this studi to compare result media Mycobacterium tuberculosis proliferation on solid media (LJ) and liquid media (MGIT) on sputum of suspected TB. The liquid culture method was Mycobacteria Growth Indicator Tube (MGIT). This method was fully automatic and non-radiometric. MGIT contains 7.0 ml of modified Middlebrook 7H9 broth. Culture results will come out in 42 days if there was no bacterial growth. Comparative research on 30 sputum suspects of TB were examined at the Surabaya Health Laboratory Center on 03 January to 20 March 2020. The sputum samples were examined through the stages of decontamination, homogenization, concentration and inoculated on LJ media and MGIT media and incubated at 370C. Identification of the colonies that grew with ZN staining and MPT 64 immunochromatography test. The results of the Wilcoxon Signed Rank Test statistical test obtained p-value of 0.157 (p> 0.05). It can be concluded that there is no difference in the culture results of Mycobacterium tuberculosis on solid media (Lowenstein Jensen) and liquid media (Mycobacteria Growth Indicator Tube). Keywords: Mycobacterium tuberculosis; Lowenstein Jensen (LJ);Mycobacteria Growth Indicator Tube (MGIT)